Psicanálise com crianças e adolescentes com impasses no laço social no contexto institucional: quando o +1 é -1 - Ragazzo, Débora Storni (2022)
Psychoanalysis has a clear political position since Freud, who defended psychoanalytic work in free clinics. Inside this perspective, the present research aims to discuss the analyst's place in the institutional context in the work with children and teenagers with impasses in the social bond. How can the analyst intervene with the team, through psychoanalysis’s ethic, in the perspective of listening to the subject of the unconscious in its singularity? To discuss this issue, Lacan’s discourse theory as possible ways of linking will be a guiding thread. Furthermore, we’ll go through some of his postulates about the treatment’s direction in psychosis’s clinic. Once the clinical case presents itself as a way of doing research in psychoanalysis and as a fundamental axis of teamwork, we´ll present two clinical pieces that point to viable inventions in the institutional context. Such pieces will enable the proposed analogy between the analyst's role in the institutional context and the +1 of the cartel. To substantiate this analogy, we will return to the collective logic that directs this training device and makes a counterpoint to the functioning of the group, guided by the Master's Discourse. In the cartel, the work has as its starting point the not knowing, since an impasse becomes an issue so that, with this, a not-all knowledge is produced. Its members are articulated based on the work’s transfer, bond that operates through the Hysteric´s Discourse, since identification occurs precisely through the hole that is not completed, by the object a. The function of +1 is to sustain the Other's inconsistency and to penetrate where the group tries to complete, thus maintaining the desiring position of the cartel’s members. Institutional impasses often arise through bureaucratization and imaginary readings, in which it is intended to impose a knowledge about the subject through the articulation of the Master's Discourse and the University Discourse. In addition, the Capitalism Discourse is present through the treatment of health as a commodity. It is the hole of the analyst, in order to subvert the dominant discourses, to promote a discursive turn. Just as the +1 has the function of ensuring that the bond in the team takes place through the Hysteric´s Speech, from the provocation and the supporting of the desire of knowing about what makes a point for each one in relation to the case. In this direction, what unites the team is the transfer of work that favors a clinical intervention in which knowledge is on the side of the subject, so that, with his unique inventions, he can border the real. Thus, the bond between the team and the subject is established through the Analytic Discourse. Finally, we propose that we do not retreat from institutions, since it is possible to find in this context a privileged space that enables that the construction of the clinical case through the circulation of subjects and different possible ties